Ajip Rosidi’s "kegelisahan" (restlessness) in between Sundanese and Indonesian literature - Muhtadin, Teddi; Moriyama, Mikihiro (Wacana, Journal of the Humanities of Indonesia, 2025)
This article explores the literary journey of Ajip Rosidi, one of Indonesia’s most prolific writers, highlighting his unique position between Sundanese and Indonesian literature. Ajip authored over 300 works spanning diverse genres, making significant contributions to literature and the preservation of cultural heritage. The article examines his ambivalence or restlessness (kegelisahan) regarding the tension between regional and national identities in literature, as exemplified in his reflections and creative output. Ajip’s early life in a linguistically mixed region of West Java laid the foundation for his literary pursuits in both Sundanese and Indonesian. His works often oscillated between traditional Sundanese forms, such as guguritan, and modern Indonesian realism, reflecting his struggle to reconcile these two literary worlds. While he initially adhered to the dominant realist framework, his engagement with Sundanese folklore and poetry emphasized the richness of non-realistic and traditional narratives. Ajip’s restlessness drove his literary creativity, leading to masterpieces like the poems “Tanah Sunda” and “Lagu Jakarta”, which depict contrasting landscapes of rural and urban life, and “Janté Arkidam”, an epic narrative symbolizing resilience. His unwavering belief in regional culture motivated him to establish the Rancagé Literary Award, promoting regional languages and literatures across Indonesia. The article concludes that Ajip’s dual identity and constant negotiation between Sundanese and Indonesian literature were not limitations but sources of profound inspiration, resulting in a legacy that continues to enrich both regional and national cultural landscapes. Ajip's early life in a linguistically mixed region of West Java laid the foundation for his literary pursuits in both Sundanese and Indonesian languages. His works often oscillated between traditional Sundanese forms, such as guguritan, and modern Indonesian realism, reflecting his struggle to reconcile these two literary worlds. While he initially adhered to the dominant realist framework, his engagement with Sundanese folklore and poetry emphasized the richness of non-realistic and traditional narratives. Ajip's restlessness drove his literary creativity, leading to masterpieces like the poems Tanah Sunda and Lagu Jakarta, which depict contrasting landscapes of rural and urban life, and Jante Arkidam, an epic narrative symbolizing resilience. His unwavering belief in regional culture motivated him to establish the Rancagé Literary Award, promoting regional languages and literatures across Indonesia. The article concludes that Ajip's dual identity and constant negotiation between Sundanese and Indonesian literature were not limitations but sources of profound inspiration, resulting in a legacy that continues to enrich both regional and national cultural landscapes.